GUARANTEES EQUIVALENT TO THE RIGHT TO A FAIR TRIAL IN THE MATTER OF CHALLENGES TO THE WITHDRAWAL OF SECURITY CERTIFICATES ISSUED BY THE OFFICE OF THE NATIONAL REGISTER OF STATE SECRET INFORMATION - Monica Cristina COSTEA (Challenges of the Knowledge Society)
Documents of a classified nature may be of a contentious nature, the paper focusing on those concerning the service relationships of active officers. In the event of a dispute arising, the question arises as to the extent to which a plaintiff is able to mount an effective defence if he cannot know their content and whether he can be granted guarantees equivalent to respect for the right to a fair trial. Restricting the lawyer's access to important documents in a case affects to a large extent the represented party. In the European countries, the situation regarding conditional access to classified documents from the point of view of lawyers and parties against whom such documents are issued is similar, in that it is recognised that the principle of adversarial proceedings and the rights of the defence must be limited because of the need to protect national security. From a procedural point of view, it is important that the general principles of adversarial proceedings, equality, orality, non-disclosure and publicity are respected in every dispute. In this context, noting the difficulties that arise in the work of the court due to restricted access to classified documents, I have tried to identify guarantees equivalent to respect for the right to a fair trial in the cases referred to in the title of the paper, analysing national case law, that provided by the ECtHR and studies of doctrine. In accordance with these, I have developed equivalent guarantees compatible with Romanian law: the possibility of challenging the classification of the document, the request for declassification of classified information, the right of the interested party to be assisted by an ORNISS-certified lawyer and the possibility for the accused to participate in proceedings which reveal the content of classified documents.